MUSIC AND EMOTION: FROM ANCIENT GREECE TO CONTEMPORANEITY (Analele Universității București.Filosofie, 2024)
Understanding how music and emotion co-vary has been the focus for many scholars for a long time, starting with the writings of Ancient Greeks to contemporary thought. Philosophers, musicologists, and cognitive scientists alike have been puzzling on the extent to which music can have an influence on how humans feel, think and act morally and ethically. Therefore, the understanding of this relation is of paramount importance as we are immersed in organized-sound contexts every day, and this has a major effect on how listeners think and act in social environments. The  current investigation aims at highlighting the development of the music and emotion relationship throughout the stylistic periods of the European space (with a short comparison to Ancient Chinese music) as a preamble for a more nuanced future research on the topic.